Natural Regeneration on Deadwood in the Primeval Forest Janj - Zoran Govedar; Nadezhda Prokhorova; Violeta Babić; Vojislav Dukić; Branko Kanjevac; Srdan Bilić (Лесной журнал, 2023)
The paper investigates the natural regeneration of downed deadwood in the Janj primeval forest. The old-growth forest is located in the southwestern part of the Republic of Srpska, which is dominated by dolomite geological base on which cambial soils were formed. The climate is perhumid and mountainous and the plantation belongs to the Piceo-Abieti-Fagetum community. The hectare contains 517 live trees with a total basal area of 53.0 m2/ha and a volume of 876 m3/ha. Twenty six downed deadwoods classified into three different degrees of decay were included in the study, where fir and spruce seedlings were found to be predominant and beech seedlings were rarely represented. The first degree of decay includes 7 (26.9 %), the second 8 (30.7 %), and the third 11 (42.3 %). The total volume of deadwood is 110.82 m3/ha with an average volume per tree of 4.2 m3/ha. The total number of seedlings on fallen dead trees is 836 seedlings (Abies alba – 89.59 %, Picea abies – 10.17 %, Fagus silvatica – 0.24 %). Fir seedlings are found on 25 fallen trees, spruce on 18 fallen trees, and beech on 2 fallen trees. Regarding quality, on average fir seedlings are better than spruce seedlings, but both species show a lot of senescence and very small size of current height increment. Most seedlings belong to the third quality class (fir – 46.2 %, spruce – 61.1 %), followed by second class (fir – 34.6 %, spruce – 22.2 %) and third class (fir – 19.2 %, spruce – 16.7 %). The total number of seedlings was found to have a statistically significant difference in the amount of downed deadwood depending on the degree of decay, and the number of seedlings depended on the degree of tree decay. The number of seedlings increased with increasing volume and length of rotten trees. Acknowledgеments: This article is the result of the project “Аdaptive management of Natural Resource of the Republic of Srpska”. We would like to thank the Ministry of Scientific and Technological Development, Higher Education and Information Society of the Republic of Srpska for their support in the realization of the project. For citation: Govedar Z., Prokhorova N., Babić V., Dukić V., Kanjevac B., Bilić S. Natural Regeneration on Deadwood in the Primeval Forest Janj. Lesnoy Zhurnal = Russian Forestry Journal, 2023, no. 5, pp. 90–102. (In Russ.). https://doi.org/10.37482/0536-1036-2023-5-90-102